The 3rd ASEAN reader - Ooi, Kee Beng; ISEAS-Yusof Ishak Institute (Singapore : ISEAS Yusof Ishak Institute, 2015)
Over the past two decades, ISEAS has compiled abridged articles that analyse key aspects of Southeast Asia's development and the ASEAN process. The ASEAN Reader was published in 1992 just as the Cold War ended, while The Second ASEAN Reader came in 2003 in the wake of the 1997 Asian crisis and the September 11 attacks in 2001. The past decade has not been spared its share of intense changes, with the rise of China and India bringing new challenges to the region's power equation, and the impact of the 2008 global financial crisis. Despite this, the momentum towards an integrated ASEAN community has been maintained. The articles in The Third ASEAN Reader study the trends and events of recent years, and discuss the immediate future of Southeast Asia.
Title from publisher's bibliographic system (viewed on 07 Jul 2017).
Keywords: Regionalism -- Southeast Asia -- 21st century; Southeast Asia -- Politics and government -- 1945-; Southeast Asia -- Economic integration; Southeast Asia -- Social conditions; ASEAN